Analisis Tunjangan Perbaikan Penghasilan (TPP) Terhadap Kinerja Aparatur Sipil Negara Setda Kabupaten Raja Ampat - Pakpahan, Ratna Rosmauli; Thasrin, Muhammad (TIN: Terapan Informatika Nusantara, 2020)
Performance is basically the responsibility of every individual who works in an institution or an organization. Good performance is the optimal result of work and in accordance with organizational standards and supports the achievement of organizational goals. Improved employee performance will bring progress to the agency (organization). Improved performance can be supported by motivation, one of which is compensation. Compensation provided within the scope of the Raja Ampat Regency Government is compensation for employee performance referred to as the Income Improvement Allowance (TPP). Where the purpose of providing Income Improvement Allowances (TPP) is expected to be a work motivation for government employees. In this study using a kuliatatif research method by using steps of data collection and through observation, interviews, and documentation. The results of this study are jasydgygwey (1) The design for the provision of income repair allowances (TPP) to the Raja Ampat District Government Civil Servant (ASN) Equipment Section is based on pre-existing allowances, namely the Regional Performance Allowance (TKD); (2) The process of granting Income Repair Allowances (TPP) based on rank and class has been running well and smoothly, namely given every month to all State Civil Servants (ASN) and honorary staff in Raja Ampat Regency, the Equipment Section by giving the amount or amount based on class , attendance / attendance and performance and loyalty. and (3) The quality of work of the State Civil Service Apparatus (ASN) of the Raja Ampat Regency Equipment Section, in general, has experienced a very significant change, namely experiencing an increase in the quality of work, in this case it can be seen from the increasing attendance of employees and an impact on the Raja Ampat economy which is getting better